2014
DOI: 10.4028/www.scientific.net/amr.971-973.284
|View full text |Cite
|
Sign up to set email alerts
|

The Research Least Squares Based on Ar Model of Glucose Prediction

Abstract: Diabetes Clinical Research important task is to monitor and prevent the occurrence of high / low blood sugar events. Glucose monitoring system (Continous Glucose Monitoring System, CGMS) is used clinically in recent years gradually new blood glucose monitoring system, by measuring the concentration of glucose in interstitial fluid glucose fluctuations throughout the day to indirectly reflect the whole picture. It can be 30 minutes early to predict blood glucose levels as well as low blood sugar warning. Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Based on AR models, Wang et al [9] adopted the least squares method and adaptive AIC criteria to optimize the AR model. The result showed that the AR prediction algorithm could effectively predict blood glucose within 30 min [10]. Subsequently, Yang et al [11] proposed a new autoregressive integrated moving average (ARIMA) model with an adaptive identification algorithm of model orders.…”
Section: Introductionmentioning
confidence: 99%
“…Based on AR models, Wang et al [9] adopted the least squares method and adaptive AIC criteria to optimize the AR model. The result showed that the AR prediction algorithm could effectively predict blood glucose within 30 min [10]. Subsequently, Yang et al [11] proposed a new autoregressive integrated moving average (ARIMA) model with an adaptive identification algorithm of model orders.…”
Section: Introductionmentioning
confidence: 99%
“…CGMS (Continuous Glucose Monitoring System) is a device that is placed on the patient and used to measure patient's blood glucose every 5 minutes. Based on the blood glucose data provided by CGMS, many kinds of prediction methods of blood glucose were proposed, such as adaptive blood glucose prediction model [ 4 ], AR (autoregressive) model [ 5 ], neural network prediction model [ 6 ], and SVM (support vector machine) model [ 7 ]. Peng et al [ 4 ] applied Kalman filter to smooth the blood glucose data from the CGMS, using AR model to build up the blood glucose prediction model, and the result showed that the blood glucose changes can be dynamically captured and the future blood glucose can be predicted.…”
Section: Introductionmentioning
confidence: 99%
“…Peng et al [ 4 ] applied Kalman filter to smooth the blood glucose data from the CGMS, using AR model to build up the blood glucose prediction model, and the result showed that the blood glucose changes can be dynamically captured and the future blood glucose can be predicted. Wang and An [ 5 ] also adopted the AR model in predicting blood glucose; the result showed that the prediction was accurate with simple calculation, but their research did not take into account the smoothness of the original data. Tresp et al [ 6 ] utilized neural network algorithm to predict blood glucose and found that their model had good tracking ability.…”
Section: Introductionmentioning
confidence: 99%